2008
DOI: 10.1002/pc.20431
|View full text |Cite
|
Sign up to set email alerts
|

Nonisothermal crystallization behavior and crystals morphology of poly(trimethylene terephthalate)/nano‐calcium carbonate composites

Abstract: Nonisothermal crystallization behavior and crystal morphology of poly(trimethylene terephthalate) (PTT) composites filled with modified nano-calcium carbonate (CaCO 3 ) had been investigated by using differential scanning calorimetry and polarized optical microscopy. The modified Avrami equation and Ozawa theory were used to investigate the nonisothermal crystallization, respectively. The particles of nano-CaCO 3 , acting as a nucleation agent in composites, accelerated the crystallization rate by decreasing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The reinforcing effect of NCC in polyethylenes and polyvinyl chloride has been demonstrated in various studies 13–16. In recent years, similar studies have been done on other thermoplastics and thermosets filled with NCC 17, 18…”
Section: Introductionmentioning
confidence: 85%
“…The reinforcing effect of NCC in polyethylenes and polyvinyl chloride has been demonstrated in various studies 13–16. In recent years, similar studies have been done on other thermoplastics and thermosets filled with NCC 17, 18…”
Section: Introductionmentioning
confidence: 85%
“…In this case, polyethylene (PE) has special position because of low cost, easy availability, light weight, high corrosion, chemical resistance, etc. which makes vast usage in different fields . One of the main deficiencies of PE is depressed critical physical properties at the elevated temperatures, which limits its applications.…”
Section: Introductionmentioning
confidence: 99%
“…1 Researchers have reported some blends and composites of PTT with other polymers, fillers or fibres. 2 17 Run et al 4 reported the isothermal crystallization and melting behavior of PTT/nano-CaCO 3 nanocomposites, the results suggest that nano-CaCO 3 increases the crystallization rate of PTT. Liu et al 5 reported the PTT/organomontmorillonite (OMMT) nanocomposites and suggest that the thermal stability and the storage modulus have been greatly improved because of the nanometer-scale layers of the OMMT.…”
Section: Introductionmentioning
confidence: 99%